QODIRIYSHUNOSLIK TARIXIGA BIR NAZAR - Reimboyeva, L.D. (SCIENCE and SOCIETY, 2018)
The article deals with studying the creative works of A.Kadyri in Uzbekistan, analyzing the writer’s creative work in the literature of the fraternal peoples as well as studying in the world literary criticism.